Caracterização morfológica e distância genética entre variedades de pimentas - Neitzke, Raquel Silviana (2008)
Peppers and sweet peppers from Capsicum genus show great genetic divergence and are an important part of the spice and fresh vegetable market in Brazil. They are closely related to the richness of Brazilian culture and belong to biodiversity patrimony, being cultivated in a huge variety of types, sizes, colors, flavors and pungencies. The success in a plant breeding program is dependent of the amplitude of genetic basis disposable. Characterization activities are very important to promote the use of germplasm by breeders. The objective of this work was to characterize and estimate genetic distance among C. baccatum landraces, using qualitative multicategorical morphological descriptors, and among accessions with ornamental potential from Capsicum Gene Bank of Embrapa Clima Temperado, using qualitative and quantitative morphological descriptors. Results indicate that use of multicategorical data was efficient to study genetic divergence among accessions of C. baccatum. Characterization of accessions with ornamental potential using qualitative descriptors was more adequate to form the groups. The grouping methods used in the study of genetic distance by quantitative descriptors were partially concordant. Results showed large genetic dissimilarity in evaluated germplasm, suggesting its use in breeding programs to different objectives, to obtain ornamental cultivars, or to develop cultivars with fruits to be consumed in natura or processed.